2008
DOI: 10.1002/hep.22061
|View full text |Cite
|
Sign up to set email alerts
|

Individualized treatment duration for hepatitis C genotype 1 patients: A randomized controlled trial

Abstract: Variable treatment duration ensures SVR rates similar to those of standard treatment duration, sparing unnecessary side effects and costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
319
3
11

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(351 citation statements)
references
References 104 publications
18
319
3
11
Order By: Relevance
“…4,5 Several studies adopting this approach have shown that extending therapy to 72 weeks may increase SVR rates in selected G1 patients. [6][7][8][9][10][11] However, the on-treatment virologic criteria used to select patients for extended therapy vary across studies.…”
mentioning
confidence: 99%
“…4,5 Several studies adopting this approach have shown that extending therapy to 72 weeks may increase SVR rates in selected G1 patients. [6][7][8][9][10][11] However, the on-treatment virologic criteria used to select patients for extended therapy vary across studies.…”
mentioning
confidence: 99%
“…Le gain est d'environ 10 % [8][9][10]. Cependant, ce traitement paraît désuet à l'heure de la trithérapie (ajout d'une antiprotéase) devenant le traitement de référence chez ces patients de génotype 1, toujours virémiques après 4 semaines de bithérapie ; -Enfin, si la virémie est toujours détectable à S24, on dispose de peu d'arguments pour poursuivre le traitement (sauf peut-être en présence d'une réponse biochimique, c'est-à-dire une normalisation des transaminases, chez des patients présentant une atteinte hépatique évoluée) mais cette proposition n'est pas consensuelle et reste un sujet non résolu ; -En présence d'un génotype 2, l'annulation de la virémie à S4 permet d'interrompre le traitement à 16 voire 12 semaines : il est vrai que, par habitude, peu de praticiens choisissent cette stratégie mais chez certains patients qui supportent mal la bithérapie, il peut s'agir d'une stratégie intéressante ; -En présence de génotype 3, la situation est intermédiaire et finalement s'apparente plus au génotype 1 qu'au génotype 2 ; il est préférable de prolonger le traitement à 48 semaines de bithérapie pégylée chez des patients en surpoids, présentant au moins un facteur de comorbidité comme l'alcool, le surpoids, ou simplement l'âge avancé (au-delà de 65 ans) ; -Le génotype 4 s'assimile au génotype 1 dans sa stratégie thérapeutique.…”
Section: La Bithérapie Traditionnelleunclassified
“…[Mangia et al 2008;Pearlman et al 2007;Berg et al 2006]. Extension of therapy in that setting has been associated with improved SVR.…”
Section: Relapsementioning
confidence: 99%